Determination of prothrombin complex hematic phase of Carrion's disease - Gastelumendi V., René (1959)
1 In the eight cases studied, Carrión Disease in its anemic phase prolongrado prothrombin time and decrease in concentration was found. 2. There is a clear relationship between the degree of thymol turbidity and prothrombin time and concentration in the anemic phase of Carrion's disease.